A complex case of severe thrombocytopenia in systemic lupus erythematosus complicated by Corynebacterium spp. infection - Akbar, Muhamad; Kalim, Handono (PT. DEKA RESEARCH INSTITUTE, 2024)
BACKGROUND: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune inflammatory disease the course of which is still indefinite. Thrombocytopenia concurrent with Corynebacterium spp.—an infrequent complication in SLE patients—is seldom reported. CASE A 34-year-old female was admitted for continuous bleeding from the gums that had been ongoing for three days. The patient had been suffering from SLE since 2018 and took immunosuppressive medication regularly. The anemia, lymphocytopenia, and severe thrombocytopenia were shown in her laboratory tests. Besides, the infection of Corynebacterium spp. was detected in the patient. In fact, hematologic abnormalities and infections in SLE patients usually mutually overlap for the reason that these conditions possess the potential to influence each other. Infection can be both the cause and result of hematologic abnormalities in SLE. Thus, the pathophysiology of hematologic abnormalities in SLE patients can often be related to the use of immunosuppressive drugs. However, some theories suppose that increased SLE activity correlates with infection occurrence in SLE—even without the use of immunosuppressive drugs. CONCLUSION Thrombocytopenia and Corynebacterium spp. infection in SLE patients is a case rarely reported, and establishing the diagnosis requires detailed examination.